Effect of Compensation on Employee Loyalty (Case Study of PT Remco Palembang) - Nando Hartoyo; Susi Handayani; Mohd Kurniawan DP (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the effect of compensation on employees’ loyalty at PT Remco Palembang. Samples were selected using sample random sampling technique. Data of 77 respondents were collected throught documentation, interviews, and questionnaires. This study implemented a simple linear regression method to analyze data. The results of the invesigation show that compensation has a significant effect on employees’ loyalty. This empirical evidence can provide benefits for PT Remco Palembang. To increase employees’ loyalty, the company should optimize compensation for employeess.